Studi Deskriptif mengenai Occupational Commitment pada Dosen Tetap Universitas “X” Kota Bandung - Meta Dwijayanthy (Humanitas (Jurnal Psikologi), 2018)
This research use descriptive desain about occupational commitment. In this research will be tell in more thorough and detail about the reasons someone choose, decide and have commitement in one job as tenure in the university. Occupational commitment as the degree of attachment to an occupation, where involvement on this occupational define by occupational commitment component that dominate (Meyer, Allen and Smith, 1993). Occupational commitment has three components, Affective Occupational Commitment, Continuance Occupational Commitment, and Normative Occupational Commitment. This research give quesionner to 80 sample from all faculty in university “x”. Validity value for Affective Occupational Commitment is between 0.515 – 0.764, 0.395 – 0.818 for continuance occupational commitment and 0.319 – 0.777 for normative occupational commitment. Then realibility value this questioner for affective occupational commitment is 0,842, continuance occupational commitment is 0,768 and normative occupational commitment is 0,8. Based on this research, 58% tenure choose, decide and have commitment in this job based on affective occupational commitment. Then 38% tenure hold in this profession based on normative occupational commitment and 4% tenure have commitment based on continuance occupational commitment. Based on this research, university must make program or policy that will made tenure more motivated to commit in this profession. Beside that, this research can be basic to other reasercher to research about factor that influence occupational commitment. Keywords: occupational, commitment and tenure